(untitled) (Asian Journal of Plant Biology, 2021)
One of the beneficial roles of the microbial population is their ability to convert toxic herbicides to lesser toxic compounds such as water and carbon (IV) oxide. Paraquat which is an acutely toxic herbicide is used on farmlands and has been found to affect human health. This study was aimed at characterizing bacteria with the potential to degrade paraquat. Previously isolated bacteria from culture collection labelled A-F were screened for their potential to degrade and utilized paraquat as the sole carbon source in Bushnell Hass agar media. Of the six isolates, isolate E (Morganella sp.) was observed to have the highest growth and tolerance to paraquat after 72 h of incubation at 37 ÂºC. Characterization study revealed that Morganella sp. can utilize and grow with optimum conditions of pH 6.5, the temperature of 30 ÂºC and can tolerate up to 400 mg/L paraquat concentration with an increase in growth as inoculum size increases. Thus, these findings showed that Morganella sp. can degrade toxic paraquat to a less toxic form and therefore can be a good isolate for the future bioremediation process of the pollutant.